Peran Perempuan Sebagai Buruh Harian Lepas dalam Meningkatkan Kesejahteraan Keluarga (Studi Kasus pada Perempuan Buruh Harian Lepas Desa Tiyingtali, Kecamatan Abang, Kabupaten Karangasem) - Widnyani, Ni Wayan; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The purpose of this study is to determine the role of women as casual daily laborers in improving family welfare in Tiyingtali Village, Abang District, Karangasem Regency. This type of research is qualitative research with case study method. The subjects of this study used 5 informants and the object was women who worked as casual daily laborers in Tiyingtali Village. The data collection method was carried out by initial observation, in-depth interviews with informants and documentation. The data analysis technique used in this study is a qualitative analysis from Miles and Huberman, starting from collecting data, reducing data, presenting data and drawing conclusions. The data validity technique in this study uses source triangulation. The results showed that women daily casual workers divide their time by prioritizing their role as housewives first and continue their role in the public sector as informal workers, namely casual daily workers and the families of women casual daily workers have been declared prosperous with the level of family welfare at the prosperous family I.